An investigation of links between metabolic rate and feed efficiency in European sea bass Dicentrarchus labrax. (8th May 2021) - Rodde, Charles; de Verdal, Hugues; Vandeputte, Marc; Allal, François; Nati, Julie; Besson, Mathieu; Blasco, Felipe R; Benzie, John A H; McKenzie, David J
Abstract: Feed efficiency (FE ) is the amount of body weight gain for a given feed intake. Improving FE through selective breeding is key for sustainable finfish aquaculture but its evaluation at individual level is technically challenging. We therefore investigated whether individual routine metabolic rate (RMR ) was a predictor of individual FE in the European sea bass Dicentrarchus labrax, a major species in European mariculture. The European sea bass has three genetically distinct populations across its geographical range, namely Atlantic (AT ), West Mediterranean (WM ), and East Mediterranean (EM ). We compared FE and RMR of fish from these three populations at 18 or 24 °C. We held 200 fish (62 AT, 66 WM, and 72 EM) in individual aquaria and fed them from ad libitum down to fasting. FI was assessed for an ad libitum feeding rate and for a fixed restricted ration (1% of metabolic body weight·day −1, with metabolic body weight = body weight 0.8 ). After being refed 12 wk in a common tank, individual RMR was measured over 36 h by intermittent flow respirometry. There was a significant effect of temperature whereby fish at 18 °C had greater mean FE ( P < 0.05) and lower RMR ( P < 0.001). There was also a significant effect of population, where AT fish had lower FE ( P < 0.05) and greater RMR ( P < 0.001) than WM and EM, at both temperatures. Despite these differences in temperature and population means, individual FE and RMR were not significantly correlated ( P > 0.05). Therefore, although the results provide evidence of an association between metabolic rate and FE, RMR was not a predictor of individual FE, for reasons that require further investigation.